Pemanfaatan Tungku Berbahan Bakar Oli Bekas untuk Peleburan Aluminium Daur Ulang dan Kajian Mikrostruktur serta Kekerasan Pasca Quenching - Yopan Rahmad Aldori; Suprapto Suprapto; Muhammad Idris; Muhammad Angga Prayoga; Evan Roland Girsang (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study investigates the use of a Waste-Oil-Fueled Furnace (WOFF) as an alternative heat source in the melting process of recycled Al-3004 aluminum. The melting was carried out using the sand casting method at a pouring temperature of approximately 730 °C, while measurements indicated the furnace could reach ±900 °C, exceeding the melting point of Al-3004 (±660 °C). The cast specimens were subsequently quenched in three media: water, oil, and air. Microstructural observations revealed that the cooling rate significantly affected crack formation: water quenching produced the largest cracks, oil quenching produced medium-sized cracks, and air cooling produced the finest cracks. Micro Vickers hardness testing supported these findings, showing significant differences in hardness values across the quenching media. Overall, the study confirms that the waste-oil-fueled furnace is an effective alternative energy-based metal-melting technology, while the choice of cooling medium plays a crucial role in controlling the material's microstructural features and mechanical properties.